Ocena sytuacji na lokalnym rynku pracy województwa wielkopolskiego w świetle różnych źródeł informacji - Gołata, Elżbieta; Dehnel, Grażyna (Evaluation of Local Labour Market Situation According to Different Data Sources, 2005)
The paper deals with the problem of convergence in measurement of unemployment at local scale in the cross-section of poviats in Wielkopolska voivodship. The measures of unemployment are estimated upon different sources of information. We take into account such databases as: registration of unemployment, Labour Force Survey, Population Census 2002 as well as indirect estimates made by Central Statistical Office and our own estimates. In the analysis we discuss availability of information concerning economic activity of local population. Different types of measures and their properties when applied at local scale are analyzed. The relation between registered unemployment and according to ILO definition is examined and conclusions for evaluation of unemployment rate are drawn.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 632-641